2018
DOI: 10.21873/anticanres.12688
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dehydrogenase Isoenzymes and Aldehyde Dehydrogenase Activity in the Serum of Patients with Non-alcoholic Fatty Liver Disease

Abstract: The activity of isozymes of class I and II alcohol dehydrogenase in patients with NAFLD is enhanced and appears to be due to the release of these isoenzymes from damaged hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Jelski et al ( 2008 ) found that class I ADH activity was considerably higher in patients with liver metastases than in subjects with primary liver cancer. In our previous study, the serum activity of total ADH, class I ADH and class II ADH was higher in patients with both alcoholic and non-alcoholic fatty liver diseases than in the control group (Jelski et al 2018a ; Wolszczak-Biedrzycka et al 2022 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Jelski et al ( 2008 ) found that class I ADH activity was considerably higher in patients with liver metastases than in subjects with primary liver cancer. In our previous study, the serum activity of total ADH, class I ADH and class II ADH was higher in patients with both alcoholic and non-alcoholic fatty liver diseases than in the control group (Jelski et al 2018a ; Wolszczak-Biedrzycka et al 2022 ).…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies have demonstrated changes in the activity of alcohol dehydrogenase (ADH), its isoenzymes and aldehyde dehydrogenase (ALDH) in the blood serum of patients with various liver diseases, including hepatitis C, liver tumors, fatty liver disease, and AIH (Chrostek and Szmitkowski 2000 ; Jelski et al 2008 , 2017 , 2018a , 2018b ). These liver diseases showed statistically higher activity of class I ADH and total ADH in the serum of patients than in healthy subjects and the results suggest a potential clinical role for ADH (especially class I ADH) as marker for liver disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Aldehyde dehydrogenase, which catalyze the oxidation of aldehydes to their corresponding carboxylic acids, play a major role in alcohol metabolism. Nonetheless, the activity of alcohol dehydrogenase in nonalcoholic fatty liver disease can also be increased (Jelski et al, 2018b). And previous studies have demonstrated the strong interactions between hepatitis virus and alcohol (McCartney et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…In our previous investigations we have found that the activity of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) were signi cantly higher in the serum of patients with different liver diseases (e.g. hepatitis C, autoimmune hepatitis, fatty liver disease) than in healthy subjects [7][8][9].…”
Section: Introductionmentioning
confidence: 99%